Delaying an infliximab infusion by more than 3 days is associated with a significant reduction in trough levels but not with clinical worsening. (March 2022) - Ben-Shatach, Zohar; Ziv-Baran, Tomer; Fudim, Ella; Yavzori, Miri; Picard, Orit; Levartovsky, Asaf; Selinger, Limor; Weiss, Batia; Kopylov, Uri; Eliakim, Rami; Ungar, Bella
Background: Higher infliximab trough levels (TLs) correlate with better clinical, inflammatory, and endoscopic outcomes among inflammatory bowel disease (IBD) patients. Although standard scheduled infliximab therapy regimen consists of infusions at pre-defined time-points (weeks 0, 2, 6, and every 8 weeks), short-period deviations from therapeutic schedule are common in 'real life', but the pharmacokinetic impact of these deviations has not been explored. In this study, we aim to determine whether short-period deviations from infusion schedule affect infliximab-TL. Methods: A retrospective analysis of all IBD patients receiving infliximab maintenance therapy every 8 weeks was conducted in a tertiary medical center. Patients with anti-drug antibodies, deliberate interval shortening and <3 sequential maintenance sera available were excluded. Associations between time since last infusion and TL were studied. Statistical analysis was performed using generalized estimating equations. Results: Out of over 10, 000 sera, 2088 sera of 302 maintenance period stable infliximab-therapy-patients met inclusion criteria (median TL 4.1 μg/mL, interquartile range (IQR) 2.3–6.5 μg/mL). A delay beyond 3 days in infusion schedule (n > 59 days since last infusion) was found to significantly affect TL (mean difference in TL 0.9 μg/mL, 95% confidence interval (CI): 0.03–1.9 μg/mL, p  < 0.04). Furthermore, among patients with delayed infusions, 80% had TL below 5 μg/mL, in comparison to 55% of patients who were not late (odds ratio (OR): 2.81, CI: 2.02–3.92, p  < 0.0001). Conclusion: Real-life delays of ⩽3 days from infusion protocol can probably be allowed. Delays >3 days culminate in measurable decrease of TL, although effect on clinical outcome is unclear. This needs to be taken into account when interpreting drug-level test results. Summary: A total of 2088 sera of 302 maintenance period inflammatory bowel disease (IBD) patients treated with infliximab were analyzed, to assess effect of small deviations from infusion schedule on TLs. A significant decline in patients' trough level (TL) was noted as early as 3 days after scheduled infusion.